The Relationship between Excessive Daytime Sleepiness and Cumulative Achievement Index of Medical Student in Atma Jaya Faculty of Medicine Batch 2018 - Jessica Clara Andriani; Jimmy Fransisco Abadinta Barus (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2022)
Introduction: Excessive Daytime Sleepiness (EDS) is the inability to maintain wakefulness and alertness during the major waking episodes of the day, with sleep occurring unintentionally or at inappropriate times almost daily for at least three months. Poor concentration is commonly reported as a symptom of EDS and frequently disrupt academic performance in the learning activity. This study aims to determine the relationship between EDS and cumulative achievement index (GPA) among medical undergraduates at Atma Jaya Catholic University of Indonesia. Methods: This research is an analytic observation research with cross-sectional data collection on 180 respondents out of the 2018 class of preclinical students at the Faculty of Medicine of the Atma Jaya Catholic University of Indonesia. The data collection methods used were the ESS (Epworth Sleepiness Scale) and cumulative achievement index (IPK) questionnaires. Demographic variables were also measured. Data were analyzed using the statistic software SPSS with a chi-square test (α ≥0,05). Results: From 180 respondents, 52,8% had EDS, 25% of the total had mild EDS, 16,1% had moderate EDS, and 11,7% with severe EDS. The cumulative achievement index found in respondents mostly ranged from moderate (43,3%) to high (42,3%). The rest had low scores. Furthermore, 25% of respondents had a high IPK score with EDS, 22% had a moderate IPK score with EDS, 5,4% had a low IPK score with EDS, 18,5% had a high IPK score without EDS, 22% had a moderate IPK score without EDS, and the rest 7,1% had low IPK score without EDS. Analysis with chi-square showed no significant relationship between EDS and IPK (P=0,425). Conclusions: There was no relationship between excessive daytime sleepiness and cumulative achievement index of medical students in Atma Jaya Faculty of Medicine and Health Batch 2018.